2019
DOI: 10.1371/journal.pone.0215362
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intensive blood pressure lowering on mortality and cardiovascular and renal outcomes in type 2 diabetic patients: A meta-analysis

Abstract: Background Previous studies have demonstrated that intensive blood pressure (BP) lowering treatment reduces the risk of all-cause mortality and provides greater vascular protection for patients with hypertension. Whether intensive BP lowering treatment is associated with such benefits in patients with type 2 diabetes mellitus remain unknown. We aimed to clarify these benefits by method of meta-analysis. Methods The PubMed, EMBASE, Science Citation Index and Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 45 publications
(31 reference statements)
1
13
0
Order By: Relevance
“…Despite the methodological differences in the included studies, our meta-analysis is in agreement with findings of a recent meta-analysis [ 18 ] that showed significant reductions in CV outcomes in a hypertensive population (including hypertension with comorbidities). Our results also agree with previous systematic reviews [ 21 , 42 ] and the most recent meta-analyses [ 17 , 19 ] in people with diabetes, cardiovascular disease and chronic kidney disease. In contrast, Takami et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Despite the methodological differences in the included studies, our meta-analysis is in agreement with findings of a recent meta-analysis [ 18 ] that showed significant reductions in CV outcomes in a hypertensive population (including hypertension with comorbidities). Our results also agree with previous systematic reviews [ 21 , 42 ] and the most recent meta-analyses [ 17 , 19 ] in people with diabetes, cardiovascular disease and chronic kidney disease. In contrast, Takami et al.…”
Section: Discussionsupporting
confidence: 93%
“…Our data were in contrast to previous studies that found low BP was associated with higher death rates, due to hypotensive effects, in the older population [ 37 , 38 ]. In hypertensive patients with diabetes or CVD risk, BP treatment has been shown to be effective in lowering the relative risk of CV events and all-cause mortality [ 17 , 19 , 21 ]. Interestingly, more recent studies [ 9 , 10 , 13 ] showed greater relative risk reduction for CV events possibly due to more aggressive BP treatment targets, replacing the placebo with a set target in the standard treatment group and more effective medication protocols.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the renal benefits of SGLT2 inhibitors cannot be ascribed to their modest action to lower blood pressure because even intensive control of blood pressure does not prevent serious renal events in type 2 diabetes. 3 SGLT2 inhibitors alleviate the increased intraglomerular filtration pressure that has been implicated in the genesis of diabetic nephropathy. Their inhibitory effects in the proximal renal tubule promote sodium delivery to the macula densa, which (through tubuloglomerular feedback) mitigates the afferent arteriolar vasodilatation produced by hyperglycemia.…”
Section: Potential Renoprotective Actions Of Sglt2 Inhibitorsmentioning
confidence: 99%
“…Wang et al [ 22 ] aimed to clarify whether intensive BP lowering was associated with benefits in patients with type 2 diabetes mellitus. They included 16 RCTs in a meta-analysis comparing intensive vs. less intensive BP lowering and found that intensive BP lowering resulted in significant reductions in the all-cause mortality risk, MACE, MI, stroke, CV death, and the progression of albuminuria.…”
Section: Intensive Bp Lowering In Diabetic Hypertensive Patientsmentioning
confidence: 99%